Tobias, Petite Sirah, 1980 - Tobias Vineyards::::::::: (1980)
Wine label for a first release 1980 Petite Sirah sourced from grapes from Jones Ranch in San Miguel, California, and produced and bottled by Tobias Vineyards in Paso Robles, California.